2016
DOI: 10.1038/srep31332
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Identification and Selective Microstimulation of Neuronal Compartments Based on Features of Extracellular Action Potentials

Abstract: A detailed, high-spatiotemporal-resolution characterization of neuronal responses to local electrical fields and the capability of precise extracellular microstimulation of selected neurons are pivotal for studying and manipulating neuronal activity and circuits in networks and for developing neural prosthetics. Here, we studied cultured neocortical neurons by using high-density microelectrode arrays and optical imaging, complemented by the patch-clamp technique, and with the aim to correlate morphological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(116 citation statements)
references
References 63 publications
8
107
1
Order By: Relevance
“…Axonal signals across a branching point were recorded by simultaneously using 841 electrodes. The action potential waveforms that have been recorded from the electrodes marked in red in Additionally, CMOS microtransducer arrays and integrated microsystems offer the capability to bidirectionally interact, also in closed loop and real time, with potentially every single neuron in a given neuronal network [17,27,44]. We investigated the relationship between stimulation location and reliability of neuronal responses to high-frequency threshold stimulations.…”
Section: Measurements and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Axonal signals across a branching point were recorded by simultaneously using 841 electrodes. The action potential waveforms that have been recorded from the electrodes marked in red in Additionally, CMOS microtransducer arrays and integrated microsystems offer the capability to bidirectionally interact, also in closed loop and real time, with potentially every single neuron in a given neuronal network [17,27,44]. We investigated the relationship between stimulation location and reliability of neuronal responses to high-frequency threshold stimulations.…”
Section: Measurements and Resultsmentioning
confidence: 99%
“…To verify that classified signals matched neuronal morphology, we superimposed spike-triggered average footprints and micrographs of lipofected neurons (Fig. 6a) [44]. We produced excitability profiles and defined stimulation thresholds for the respective electrodes.…”
Section: Measurements and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[60]) is immediately available within our framework: indeed, preliminary results with denser arrays (30μm spacing between electrodes) revealed that due to the increased proximity between the stimulating electrode and its neighboring electrodes, those electrodes also possessed large artifacts and were subject to the effect of breakpoints. Then, we can proceed exactly as we did in Simplifications and extensions for local return, by considering different models for the stimulating electrode and its neighbors.…”
Section: Limitationsmentioning
confidence: 99%